Symbol Between Meaning and Expression According to Hegel - Abbas, Boushra (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research handled the concept of symbol as mentioned in the Hegelian Phenomenology which neglects the reading of this relation between the symbol and the sacred. That is because this relation seems to be normative one following one specific culture which makes it difficult to have one interpretative basis for the symbol especially when one talks about the symbol prior to art. This means when we trace it down to Hegel on the natural level prior to humans' concern to create a derivative nature out of the first nature. All has been discussed in relation to the relation of symbol to signs and their interpretative nature. This Hegelian Phenomenology talks about this false interpretation, focusing on future interpretation rather than the previous past one; the one that has later been justified in some schools of interpretation and hermeneutics. Moreover, in regard to interpretation and meaning, this phenomenology practices interpretation within philosophic discourse mechanisms where it appears as an interpretive work. Afterwards, it proceeded to the concept of expression, its relation to the spirit phenomenology and how expression stands as a thread of unification of the internal thread in the philosophic discourse. On the other hand, in interpretation, it similarly went back to Paul Ricor and based its study on this united pattern within the philosophic discourse. Expression has presented the concept of absolute in phenomenology which had an effect on the interpretive theory through the concept of expression be it one whole unification that helped rationalizing the symbol within the philosophic discourse.